Takeover Defenses of IPO Firms - Field, Laura Casares; Karpoff, Jonathan M. (Journal of Finance, 2002)
ABSTRACT Many firms deploy takeover defenses when they go public. IPO managers tend to deploy defenses when their compensation is high, shareholdings are small, and oversight from nonmanagerial shareholders is weak. The presence of a defense is negatively related to subsequent acquisition likelihood, yet has no impact on takeover premiums for firms that are acquired. These results do not support arguments that takeover defenses facilitate the eventual sale of IPO firms at high takeover premiums. Rather, they suggest that managers shift the cost of takeover protection onto nonmanagerial shareholders. Thus, agency problems are important even for firms at the IPO stage.